2010
DOI: 10.1136/hrt.2010.211607
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cardiac resynchronisation therapy on dilated cardiomyopathy with isolated ventricular non-compaction

Abstract: Patients with IVNC-DCM had greater LV reverse remodelling after CRT than patients with DCM. The greater the area of non-compaction (higher number of IVNC segments) the greater the chance of achieving CRT response and greater LV reverse remodelling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 21 publications
2
41
0
5
Order By: Relevance
“…On the other hand, the hypertrabeculation phenotype can be observed in heart diseases other than DCM, such as hypertrophic cardiomyopathy [21], congenital heart diseases [22], or neuromuscular disorders [17]. Some authors have suggested that ventricle dilatation and the separation of the inner myocardial layer make trabeculation more visible [23]. Interestingly, in our study mid-wall fibrosis, which is a characteristic feature of DCM, was found less frequently in patients with high degrees of trabeculation.…”
Section: Discussionmentioning
confidence: 39%
“…On the other hand, the hypertrabeculation phenotype can be observed in heart diseases other than DCM, such as hypertrophic cardiomyopathy [21], congenital heart diseases [22], or neuromuscular disorders [17]. Some authors have suggested that ventricle dilatation and the separation of the inner myocardial layer make trabeculation more visible [23]. Interestingly, in our study mid-wall fibrosis, which is a characteristic feature of DCM, was found less frequently in patients with high degrees of trabeculation.…”
Section: Discussionmentioning
confidence: 39%
“…There is some evidence that early initiation of typical HF treatment in LVNC patients with or without clinical symptoms, especially in the beginning of left ventricular dysfunction, could be beneficial and delay fully-expressed HF clinical presentation [2]. Some authors have demonstrated that cardiac resynchronisation therapy can results in improvement of left ventricular function in patients with a dilated left ventricle coexisting with LVNC [1]. Due to the high risk of sudden cardiac death caused by arrhythmias an implantation of cardioverter-defibrillator device (ICD) based on conventional criteria used in HF should be always considered.…”
Section: Discussionmentioning
confidence: 99%
“…Biventricular pacing is a form of cardiac stimulation, referred to as cardiac resynchronization therapy (CRT), that may improve cardiac function in the case of heart failure, low ejection fraction and ventricular dyssynchrony [25]. …”
Section: Cardiac Manifestations Of Laminopathies and Clinical Decisiomentioning
confidence: 99%
“…The beneficial effects of CRT on LV reverse remodeling and systolic function are very clear in dilated cardiomyopathy with LV non compaction, a setting where a high proportion of patients may exhibit a so called ‘super-response’, with the evidence that the greater the area of noncompaction (higher number of non-compacted segments) the greater the chance of achieving a favourable CRT response and greater LV reverse remodeling [25]. …”
Section: Dilated Cardiomyopathymentioning
confidence: 99%